Analisis pemanfaatan media sosial sebagai sarana pemasaran Perpustakaan Umum daerah Kota Batu - Hasanah, Hamidatun (Maliki Interdisciplinary Journal, 2024)
The development of information and communication technology continues to progress and improve. Humans can easily access the information they need wherever and whenever. Easy and fast access to information makes humans have the habit of accessing information via smartphones. Public libraries as information provider institutions must be able to continue to exist amidst the development of this era. Public libraries must have competitiveness and be able to adapt to existing technological developments. Social media is the most popular thing nowadays, especially by young people. Based on these conditions, public libraries utilize social media for marketing media so that they can exist in the millennial generation. Public library marketing through social media is carried out to introduce existing facilities and services, so that the library does not lose its fans or visitors. In this article, we will discuss how to use social media in the Batu City public library. The research method used is a qualitative method. Data collection was carried out by indirect observation and literature study from previously published articles with the same interesting topic. The data used is secondary data obtained from national journal articles. The results of the study found that the Batu City regional public library utilizes social media YouTube, Instagram, and Facebook as a marketing tool to be known by many people.